The Crown's Fiduciary Obligations in the Era of Aboriginal Self-Government - McNeil, Kent (Osgoode Digital Commons, 2009)
This article confronts the contention that the Crown’s fiduciary obligations are incompatible with Aboriginal self-government. Relying on Supreme Court decisions, it argues instead that the Crown has a fiduciary duty to support Aboriginal autonomy. Consequently, past infringements of the inherent right of self-government by imposition of the band council system violated the Crown’s fiduciary obligations. The appropriate remedy for this breach is restitution, involving federal assistance to enable First Nations to restore and maintain their capacity to govern themselves in accordance with their own traditions and present-day aspirations.